Should I stay or should I go? Mycorrhizal plants are more likely to invest in long-distance seed dispersal than non-mycorrhizal plants - Correia, Marta (2018)
Seed dispersal and mycorrhizal associations are key mutualisms for the functioning and regeneration of plant communities; however, these processes have seldom been explored together. We hypothesised that obligatory mycorrhizal plants will be less likely to have long-distance dispersal (LDD) syndromes since the probability of finding suitable mycorrhizal partners is likely to decrease with distance to the mother plant. We contrasted the mycorrhizal status and LDD syndromes for 1960 European plant species, using phylogenetically corrected log-linear models. Contrary to our expectation, having specialised structures for LDD is more frequent in obligate mycorrhizal plants than in non-mycorrhizal plants, revealing that lack of compatible mutualists does not constrain investment in LDD structures in the European Flora. Ectomycorrhizal plants associated with wind-dispersing fungi are also more likely to have specialised structures for wind dispersal. Habitat specificity and narrower niche of non-mycorrhizal plants might explain the smaller investment in specialised structures for seed dispersal.